PENGARUH MEDIA POP UP BOOK TERHADAP KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN DI TK AISYIYAH PASAR BARU - Putri, Helena Anggia; M. Pd, Dra. Zulminiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the fact that children's numeracy skills have not yet developed, children are not yet able to sort numbers, match numbers with objects, children are not yet able to compare the size of the value of numbers and the media used does not interest children in learning to count at school. This study aims to determine the effect of using pop-up book media on children's numeracy skills at Aisyiyah Pasar Baru Kindergarten. This study uses a quantitative approach with the Quasy Experiment method. The population of the study was all children at Aisyiyah Pasar Baru Kindergarten, namely class B1 as the experimental class and class B2 as the control class, each of which consisted of 13 children. The data collection technique used test questions. Then the data was processed with a normality test, homogeneity test, and hypothesis test with the help of the SPSS 26.0 for windows application. Based on data analysis, the normality test obtained data in the experimental class and control class were normally distributed. In the homogeneity test, the data was homogeneous. In the hypothesis test with a paired sample t-test, the sig value (2-tailed) was 0.000 <0.05. Thus it is concluded that there is a significant (real) influence between the learning conducted by researchers in the experimental class with pop-up book media to improve children's arithmetic skills at Aisyiyah Pasar Baru Kindergarten.